PEMBAHARUAN HUKUM PIDANA DI DALAM KUHP SEBAGAI UPAYA KESELARASAN SISTEM PEMIDANAAN ATURAN HUKUM DENGAN UNDANG UNDANG KHUSUS DI LUAR KUHP - Suputra, Bram; Agung, I Gusti Nyoman (Kertha Negara : Journal Ilmu Hukum, 2013)
The establishment of a special law concerning crimes other than those stipulatedin the Code of Criminal Law (KUHP) is justified by the Criminal Code. However, manylaw outside the Criminal Code does not distinguish or qualify the crime, whether thecrime including crime, or a violation of, and does not list rules punishment orapplication. This is in contrast with what is stipulated in the Criminal Code. Thesedistinctions affect the criminal system is implemented in such offenses. So it needs to beexplained further how the role of the reform of criminal law in the Criminal Code as anattempt alignment system of criminal law with laws specifically outside of the Criminal Code.
Keywords: System Punishment, Renewal, Kuhp